Establishing Shot Type Affects Arousal and Cognitive Load During Transitions Between Novel Interior Locations in Films - Brighter, Grant; Rader, Nancy (Frontiers in Human Neuroscience, 2019)
An “establishing shot” prefaces a scene in a movie with a wide shot of the scene’s location. It is meant to help viewers process a shift to a new location. Establishing shots can depict the actors in the space in which they will be acting, the exterior of a building, or the larger geographic context of the scene. While use of an establishing shot is standard filmmaking practice, some argue that establishing shots are unnecessary. This study sought to investigate how effective four types of establishing shots are at helping viewers process location shifts. Pupil diameter was recorded using a MangoldVision eye tracking system as a measure of arousal and cognitive load. Oxygenation levels in the prefrontal cortex provided an additional measure of cognitive load assessed through functional near infrared spectroscopy (fNIRS). We expected scene transitions to be followed by transient increases in pupil diameter and oxygenation levels, suggesting increased cognitive load and arousal. We predicted that participants should experience less cognitive load and arousal after a transition to a new scene when that scene has been prefaced with an establishing shot and that these effects would be greatest for establishing shots that depict actors. We found that geographic establishing shots produced significantly lower average pupil diameter than all other establishing shot types and the use of no establishing shot. Actors establishing shots elicited significantly lower average pupil diameter values than the use of no establishing shot. Maximum and average oxygenation values for the actors establishing shot condition were significantly higher than for the exterior establishing shot condition. An alpha level of 0.05 was used for all analyses. These results suggest differences between pupil diameter and fNIRS in terms of the psychological phenomenon they measure, and may inform the design of future films.